2009
DOI: 10.1523/jneurosci.5302-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Mediated Degradation of β-Amyloid via an Apolipoprotein E Isoform-Dependent Mechanism

Abstract: Recent studies suggest that bone marrow-derived macrophages can effectively reduce ␤-amyloid (A␤) deposition in brain. To further elucidate the mechanisms by which macrophages degrade A␤, we cultured murine macrophages on top of A␤ plaque-bearing brain sections from transgenic mice expressing PDAPP [human amyloid precursor protein (APP) with the APP 717VϾF mutation driven by the platelet-derived growth factor promoter]. Using this ex vivo assay, we found that macrophages from wild-type mice very efficiently de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 43 publications
2
63
0
Order By: Relevance
“…Results from the present study show that human macrophages can avidly internalize Aβ and that this process has an effect on MMP-9 activation, in agreement with previous results in mice peritoneal macrophages [19]. However, our study shows that in human macrophages, in contrast to the results in mouse peritoneal macrophages, Aβ peptides exerted an upregulatory effect not only on MMP-9, but also on MMP-2 expression and abundance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results from the present study show that human macrophages can avidly internalize Aβ and that this process has an effect on MMP-9 activation, in agreement with previous results in mice peritoneal macrophages [19]. However, our study shows that in human macrophages, in contrast to the results in mouse peritoneal macrophages, Aβ peptides exerted an upregulatory effect not only on MMP-9, but also on MMP-2 expression and abundance.…”
Section: Discussionsupporting
confidence: 91%
“…Most of these interactions are pathological for the cells. It has been previously reported that macrophages have the ability to internalize and degrade Aβ in an apoE-facilitated manner [19]. These authors suggested that macrophage-mediated Aβ degradation is, in part, mediated by secretion of matrix metalloproteinase-9 (MMP-9).…”
Section: Introductionmentioning
confidence: 99%
“…In transgenic mice models (see Table 6), MMP-9 expression is further triggered by neurons upon exposure to Ab derived peptides and macrophages induces MMP-9 expression to get Ab clearance (Deb et al, 2003;Guo et al, 2006;Zhao et al, 2009).…”
Section: 242mentioning
confidence: 99%
“…The apoE gene encodes a 34-kDa protein that is expressed throughout the brain. It is synthesized and secreted by astrocytes and microglia and involved in the regulation of the lipid metabolism (Boyles et al, 1985;Xu et al, 2006;Riddell et al, 2008;Zhao et al, 2009 (Urosevic and Martins, 2008). Two recent studies provided novel molecular mechanism for the impaired Aβ clearance that may explain the strong isoform-dependent effects of ApoE in determining the genetic risk for AD.…”
Section: Functional Link Betweenmentioning
confidence: 99%